2009
DOI: 10.1088/1742-6596/161/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Problems and paradoxes of the Lifshitz theory

Abstract: The problems and paradoxes of the Lifshitz theory in application to real dielectric and semiconductor materials are reviewed. It is shown that the inclusion of drift current of conduction electrons into the model of dielectric response results in contradictions with both thermodynamics and experimental data of different experimental groups. Physical reasons why the problems and paradoxes arise are analyzed and found to be connected with the violation of basic applicability condition of the Lifshitz theory, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…It was shown, however, that the modification of the TM reflection coefficient in accordance with Eq. (40) leads to the violation of the Nernst heat theorem for those dielectric materials whose charge carrier density does not vanish when T → 0 and conductivity vanishes due to the vanishing mobility (Klimchitskaya, 2008;. For metals with perfect crystal lattices this approach violates the Nernst theorem as discussed above (Mostepanenko et al, 2009).…”
Section: Real Metalsmentioning
confidence: 99%
“…It was shown, however, that the modification of the TM reflection coefficient in accordance with Eq. (40) leads to the violation of the Nernst heat theorem for those dielectric materials whose charge carrier density does not vanish when T → 0 and conductivity vanishes due to the vanishing mobility (Klimchitskaya, 2008;. For metals with perfect crystal lattices this approach violates the Nernst theorem as discussed above (Mostepanenko et al, 2009).…”
Section: Real Metalsmentioning
confidence: 99%
“…It is pertinent to note that the Boltzmann transport equation used to derive the reflection coefficients r mod TM,TE (iξ) describes only nonequilibrium processes which must be accompained by an increase of entropy. 91 It was shown that the modified theory of the van der Waals and Casimir force violates the Nernst heat theorem for several classes of dielectric materials 5,16,41,43,44,92 and for metals with perfect crystal lattices. 5,16,42,44,93 There were a few dissenters from this result 40,[94][95][96][97] in application to dielectric materials.…”
Section: Comparison With the Modified Lifshitz Theorymentioning
confidence: 99%
“…However, in the case of metals with perfect crystal structure (which is the basic model used in condensed-matter physics) and for dielectrics, a satisfactory solution was not found. This even resulted in the attempts [22,23] to modify the Lifshitz theory, and this led to a controversial discussion in the literature [6,11,[24][25][26][27][28][29][30][31]. From the experimental side, it was shown that data exclude the Lifshitz theory if the role of conduction electrons is taken into account by means of the dissipative Drude model.…”
Section: Introductionmentioning
confidence: 99%